IMPLEMENTASI DOUBLE CAESAR CIPHER MENGGUNAKAN ASCII - Ahmad Tantoni; Mohammad Taufan Asri Zaen (Jurnal Informatika dan Rekayasa Elektronik, 2018)
In this paper, it will discuss about the merger between caesar cipher with caesar cipher or called double caesar cipher. In this study will show the design of the double caesar cipher algorithm, in order to secure the database given the database login user form to make it safer. Double caesar cipher is the development of symmetrical caesar cipher algorithms. The encryption and description process has the same key, each of which has a key. Not only that, the research will also show the double caesar cipher algorithm script using the ASCII (American Standard Code for Information Interchange) table and also in the .php programming language (hypertext preprocessor), then how do I run the double caesar cipher, the last is trying to enter plaintext into the double caesar cipher program then convert it to ciphertext and vice versa from ciphertext to plaintext again.